Care coordinator delivered Method of Levels therapy for people reporting first-episode psychosis: Experiences and views of service user, care coordinator, and team manager participants of the CAMEO trial - Robert Griffiths; Sara Tai; Susan Ormrod; Natalie Welsh; Adam Jones; Jasper Palmier-Claus; James Dixon; Alison Dawber; Karina Lovell (BMC Psychiatry)
Abstract Background Without effective and timely support, psychosis can lead to negative personal, economic, and societal outcomes. Care coordinators play a key role in the delivery of early intervention in psychosis services, which aim to improve outcomes and promote recovery for people experiencing first-episode psychosis. Enhancing the support offered by care coordinators could improve outcomes and reduce levels of service user disengagement. This study aimed to understand participants’ views on the acceptability of a transdiagnostic talking therapy, called Method of Levels (MOL), delivered by care coordinators in early intervention in psychosis services. It also sought to understand participants’ experiences of the MOL training and supervision programme, and to identify any barriers that might impact on the implementation of the approach in routine practice. Methods Semi-structured interviews and focus groups were conducted with service users (n = 14), care coordinators (n = 6), and team managers (n = 6) from early intervention in psychosis services. Interviews and focus groups were transcribed and reflexive thematic analysis was used to analyse the data. Results Three themes were identified: ‘Digging deeper to find my own solutions’; (2) ‘Prepared for practice?’; and (3) ‘Levels of implementation’. Participants described how the use of MOL enabled service users to explore problems in greater depth and generate their own solutions to these. Care coordinators generally reported feeling ready to deliver the intervention after attending MOL training and were able to integrate the approach into their practice in a flexible way. High workloads limited care coordinators’ capacity to attend MOL supervision regularly, reducing their overall confidence in delivering the approach. This impacted on the degree to which care coordinators used MOL in their practice. Conclusions Findings suggest that MOL delivered by care coordinators could be a helpful approach for people experiencing first-episode psychosis. Care coordinators found it difficult to attend clinical supervision, however, which represents a barrier to implementation. This issue will need to be addressed before care coordinator delivered-MOL for first-episode psychosis can be evaluated in a larger study or implemented in practice.